1993
DOI: 10.1091/mbc.4.8.791
|View full text |Cite
|
Sign up to set email alerts
|

Divergent fates of P- and E-selectins after their expression on the plasma membrane.

Abstract: P-selectin and E-selectin are related adhesion receptors for monocytes and neutrophils that are expressed by stimulated endothelial cells. P-selectin is stored in Weibel-Palade bodies, and it reaches the plasma membrane after exocytosis of these granules. E-selectin is not stored, and its synthesis is induced by cytokines. We studied the fate of the two proteins after their surface expression by following the intracellular routing of internalized antibodies to the selectins. By immunofluorescent staining, P-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
114
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 53 publications
2
114
0
3
Order By: Relevance
“…CD63-specific antibodies are internalized and travel through the early and then the late endosomal compartments before eventually reaching the WPB 10 . Likewise, internalized anti-P-selectin antibodies can be found in WPB following transport through endosomes 9 . However, differences appear to exist between the transport of endosomal CD63 and P-selectin to WPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD63-specific antibodies are internalized and travel through the early and then the late endosomal compartments before eventually reaching the WPB 10 . Likewise, internalized anti-P-selectin antibodies can be found in WPB following transport through endosomes 9 . However, differences appear to exist between the transport of endosomal CD63 and P-selectin to WPB.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody uptake experiments revealed that plasma membrane CD63 is internalized to late endosomes and a fraction is then transported to WPB. Endothelial activation, in turn, leads to WPB exocytosis and cell surface presentation of CD63, indicating that this tetraspanin cycles between late endosomes and the plasma membrane via WPB 9,10 .…”
mentioning
confidence: 99%
“…Following the stimulation of these cells with thrombin or other agonists, it is redistributed to the plasma membrane (24 -26) and then rapidly internalized (27)(28)(29)(30)(31). When heterologously expressed in cells lacking a regulated secretory pathway, P-selectin is constitutively transported to the cell surface and efficiently endocytosed to lysosomes for degradation (10,28).…”
mentioning
confidence: 99%
“…P-selectin disappears from the endothelial cell surface after 60-75 min of stimulation (Hattori et al, 1989a;Sugama et al, 1992) and is believed to be internalized and returned to the Golgi region and Weibel-Palade bodies (Subramaniam et al, 1993;Disdier et al, 1992;Green et al, 1994).…”
mentioning
confidence: 99%